The modelling of factors determining the goods and traffic flows movement in a logistical system - Jaržemskis, Andrius (Transport, 2003)
The purpose of this atticle is to model the factors determining the goods traffic along the logistical channels located in various geopolitical regions on the basis of the transport network. The attention is focused on theoretical presumption of logistical channels formation in a logistical system. In this modeling the factors which determine the formation of the goods flow along the subsystems of the entire logistical system from the geopolitical point of view are defined. In this model the competitiveness of a logistical channel is determined by its technological, economical, legal characteristics as well as the length of the entire channel. The states, having the model provided, can evaluate the characteristics of the elements of the logistical channel and seek for the optimum ways to improve them. While planning the allocation of investments to improve the characteristics of separate elements of a logistical channel, it is a matter of utmost impmtance to consider the characteristics and their prospects of the entire logistical channel, a part of which stretches along the other states. It is very important for the Baltic States which are situated at the intersection of transit goods flows and logistical channels.First Published Online: 19 Dec 2011